2017
DOI: 10.15511/ejcm.17.00467
|View full text |Cite
|
Sign up to set email alerts
|

Correlations between hematological indicators and other known markers in acute coronary syndromes

Abstract: Introduction:Recently, many hematologic markers have identified as prognostic and diagnostic indicators in different acute coronary syndrome (ACS) patients. In particular, neutrophil / lymphocyte ratio (NLR) and platelet / lymphocyte ratio (PLR) are recognized as markers in the diagnosis and prognosis of ACS. In this study, our aim was to investigate the correlation between the diagnostic yield of PLR and NLR values and other markers such as troponin in all ACS patients. Material and methods:319 patients admit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
3
0
7

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 22 publications
2
3
0
7
Order By: Relevance
“…The previous study also showed PLR is elevated in both ACS and SCAD compared to healthy controls [32], [37], [38]. This study shows that elevated PLR is mainly due to lower lymphocyte count.…”
Section: Discussionsupporting
confidence: 67%
See 3 more Smart Citations
“…The previous study also showed PLR is elevated in both ACS and SCAD compared to healthy controls [32], [37], [38]. This study shows that elevated PLR is mainly due to lower lymphocyte count.…”
Section: Discussionsupporting
confidence: 67%
“…In this research, both NLR and PLR are higher in ACS compared to SCAD. Similarly, the previous study showed NLR is elevated in both ACS and SCAD compared to healthy controls [32], [33], [34]. Higher NLR in ACS is related to acute and higher-grade inflammation response which neutrophils act as acute phase pro-inflammatory agents and lymphocytes as anti-inflammatory agents.…”
Section: Discussionsupporting
confidence: 57%
See 2 more Smart Citations
“…We did not include patients over 70 years old based on the study of Chenevier-Gobeaux et al (24) They revealed significantly increased PSP levels in patients older than 70 years old compared to patients younger than 70 years old. (24) Biochemical and hematological markers are important predictors in development and diagnosis of cardiovascular diseases (25,26). In our previous study, we also reported that PSP levels were significantly elevated in acute ST elevation myocardial infarction patients together with high sensitivity troponins, which may be a novel supporting marker for acute myocardial infarction.…”
Section: Discussionmentioning
confidence: 91%